Utility of vertebral left atrial size and vertebral heart size to aid detection of congestive heart failure in dogs with respiratory signs - Evan S. Ross; Lance C. Visser; Nicholas Sbardellati; Brianna M. Potter; Alex Ohlendorf; Brian A. Scansen (Journal of Veterinary Internal Medicine, 2023)
Abstract Background Differentiating cardiogenic vs noncardiogenic causes of respiratory signs can be challenging when echocardiography is unavailable. Radiographic vertebral left atrial size (VLAS) and vertebral heart size (VHS) have been shown to predict echocardiographic left heart size, with VLAS specifically estimating left atrial size. Hypothesis/Objectives Compare the diagnostic accuracy of VLAS and VHS to predict left‐sided congestive heart failure (CHF) in dogs presenting with respiratory signs. Animals One‐hundred fourteen dogs with respiratory signs and radiographic pulmonary abnormalities. Methods Retrospective cross‐sectional study. Dogs had to have an echocardiogram and thoracic radiographs obtained within 24 hours. Diagnosis of CHF was confirmed based on the presence of respiratory signs, cardiac disease, LA enlargement, and cardiogenic pulmonary edema. Results Fifty‐seven dogs had CHF and 57 did not have CHF. Compared to VHS (area under the curve [AUC] 0.85; 95% confidence interval [CI], 0.77‐0.91), VLAS was a significantly (P = .03) more accurate predictor of CHF (AUC, 0.92; 95% CI, 0.85‐0.96). Optimal cutoff for VLAS was >2.3 vertebrae (sensitivity, 93.0%; specificity, 82.5%). Murmur grade (P = .02) and VLAS (P < .0001) were independently associated with CHF and VHS was not. Increased VHS (54%) was significantly (P = .01) more common than increased VLAS (24%) in dogs without CHF. Results were similar in a subsample of older and smaller dogs. Conclusions and Clinical Importance When echocardiography is unavailable, VLAS and murmur grade have clinically utility to aid in differentiating cardiogenic from noncardiogenic respiratory signs. These findings might be especially useful to help rule out CHF in dogs with increased VHS that present with respiratory signs.